Cerebral glucose metabolism in bipolar disorder: A voxel‐based meta‐analysis of positron emission tomography studies. Issue 5 (26th March 2021) - Wu, Chujun; Ren, Chutong; Teng, Ziwei; Li, Sujuan; Silva, Floyd; Wu, Haishan; Chen, Jindong
Abstract: Background: Previous positron emission tomography studies have reported the changes of cerebral glucose metabolism in bipolar disorder. However, the findings across studies remain controversial, containing differing results. Methods: A systematic literature search of the PubMed, Embase, Cochrane Library, and Web of Science databases was conducted. We conducted a voxel‐wide meta‐analysis of cerebral glucose metabolism studies, using the seed‐based mapping approach, in patients with bipolar disorder (BD). Results: We identified 7 studies suitable for inclusion, which included a total of 126 individuals with BD and 160 healthy controls. The most consistent and robust findings were an increase in cerebral glucose metabolism in the right precentral gyrus and a decrease in the left superior temporal gyrus, left middle temporal gyrus, and cerebellum. Additionally, the sex distribution and illness duration had significant moderating effects on cerebral glucose metabolism alterations. Conclusions: Cerebral glucose metabolism alterations in these brain regions are likely to reflect the disease‐related functional abnormalities such as emotion and cognition. These findings contribute to a better understanding of the neurobiological underpinnings of bipolar disorder. Limitations. This study was done at a study level and cannot be addressed at the patient level. Subgroup analysis of BD I and BD II is not possible due to limited literature data. Abstract : The changes of cerebral glucose metabolism in bipolar disorder remains differences. Our meta‐analysis used the seed‐based mapping approach and found that cerebral glucose metabolism alterations are likely to reflect the disease‐related functional abnormalities.